Developing English Learning Materials for Islamic Boarding Schools in indonesia - Muhaemin; Fadhliyah Rahmah Muin (Indonesian TESOL Journal, 2024)
This study aims to develop contextually responsive English learning materials for students in Indonesian Islamic boarding schools (pesantren) through the integration of the English for Specific Purposes (ESP) framework and the ADDIE instructional design model. A comprehensive needs analysis was conducted involving 55 students at Pondok Pesantren Nurul Junaidiyah Lauwo to examine their target needs, linguistic deficits, preferred input types, and favored task formats. The results indicate considerable skill-related challenges, particularly in speaking, where students struggled with pronunciation (44.44%) and idea expression (33.33%). Reading difficulties were also prominent, primarily due to limited vocabulary knowledge (66.66%). Listening challenges included difficulty comprehending native-speaker input (44.44%), while writing issues centered on sentence construction (33.33%). Students demonstrated a strong preference for materials grounded in their daily pesantren routines, such as dormitory-based activities (44.44%) and religious practices, and favored multimodal input types, including short texts accompanied by visuals (55.55%) and illustrated listening materials (77.77%). Interactive tasks—particularly interviews (66.66%) and review-based activities (55.55%)—were perceived as the most engaging. In response to these findings, a set of tailored English learning materials was developed, incorporating culturally relevant vocabulary, task-based speaking activities, pronunciation support, integrated reading–listening input, and scaffolded writing practices. Expert validation confirmed the materials’ relevance, pedagogical soundness, and cultural appropriateness. Overall, the study underscores the critical importance of localized and context-sensitive materials in enhancing learners’ motivation, linguistic accuracy, and communicative competence in Islamic boarding school settings, while also offering recommendations for broader implementation and future refinement.